The impact of service quality of Celcom broadband towards customer satisfaction in Sabah Market / Hafizah Ahmad Munir - Ahmad Munir, Hafizah (2015)
This is a descriptive research design conducted to identify the impact of service quality of Celcom broadband towards customer satisfaction in Sabah market. A structured questionnaire consisting of service quality dimensions of reliability, responsiveness, assurance, empathy and tangible was used to collect data needed. Simple random sampling technique was used to select 351 Celcom broadband users in Kota Kinabalu, Sabah area to measure their satisfaction level towards Celcom service quality. As the broadband is conscious and difficult to be predicting, this study want to identify the most dimension of service quality that impact on customer satisfaction on broadband. Collected data were analyzed using frequency and percentage distribution and have been interpreted by statistical analysis software of SPSS. This study will beneficial to future researcher and companies that interested in entering the market especially in broadband's local market. It will help to have better understanding especially on the impact of service quality on customer satisfaction towards Celcom broadband.